login
a(n) = (n+1)^2 * (n!)^3 * Sum_{k=0..n} 1/((k+1)^2 * (k!)^3).
3

%I #10 Jan 05 2024 07:56:57

%S 1,5,91,4369,436901,78642181,23120801215,10358118944321,

%T 6712061075920009,6040854968328008101,7309434511676889802211,

%U 11578144266496193446702225,23480476572454280309912112301,59828254306613506229656062142949

%N a(n) = (n+1)^2 * (n!)^3 * Sum_{k=0..n} 1/((k+1)^2 * (k!)^3).

%F a(n) = (n+1)^2 * n * a(n-1) + 1.

%o (PARI) a(n) = (n+1)^2*n!^3*sum(k=0, n, 1/((k+1)^2*k!^3));

%Y Cf. A217284, A368775.

%Y Cf. A368770.

%K nonn

%O 0,2

%A _Seiichi Manyama_, Jan 05 2024